2017
DOI: 10.1002/jso.24735
|View full text |Cite
|
Sign up to set email alerts
|

Tc‐99m tilmanocept versus Tc‐99m sulfur colloid in breast cancer sentinel lymph node identification: Results from a randomized, blinded clinical trial

Abstract: The number of identified SLNs did not differ significantly between TcTM and TcSC. Given that no significant technical advantages exist between the two agents, surgeons should choose a radiopharmaceutical based on cost and side effect profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…Additionally, Unkart et al found no statistical differences in breast cancer patients concerning number of hotspots, number of removed SLNs, time to surgical removal, or number of blue nodes for [ 99m Tc]Tc-Tilmanocept compared with [ 99m Tc]Tc-sulphur colloid [23]. However, this study was not especially designed for analyzing differences regarding SLN identification.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, Unkart et al found no statistical differences in breast cancer patients concerning number of hotspots, number of removed SLNs, time to surgical removal, or number of blue nodes for [ 99m Tc]Tc-Tilmanocept compared with [ 99m Tc]Tc-sulphur colloid [23]. However, this study was not especially designed for analyzing differences regarding SLN identification.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, another study using 99m Tc-tilmanocept observed a reduction of false negative findings to 2.56% [ 18 ], demonstrating better results. However, the difference between 99m Tc-tilmanocept and 99m Tc-sulfur colloid has been part of a randomized, blinded clinical trial in breast cancer [ 22 ]. This study could not find any differences between these tracers.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Historically, the standard radiotracer used in the United States has been Tc-99m sulfur colloid (TcSC), which is passively transported by the lymphatic system based on molecular weight (100-220 nm). 4,6 In contrast, 99mTctilmanocept (TcTM) is a small (7 nm) radiotracer approved by the Food and Drug Administration in 2013 that targets the mannose CD206 receptor within the macrophages of lymph nodes. [5][6][7] In a phase 1 clinical trial in breast cancer patients, TcTM demonstrated faster injection site clearance and equivalent primary sentinel lymph node uptake when compared to TcSC, which has significant implications for surgical planning, patient convenience and health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 In contrast, 99mTctilmanocept (TcTM) is a small (7 nm) radiotracer approved by the Food and Drug Administration in 2013 that targets the mannose CD206 receptor within the macrophages of lymph nodes. [5][6][7] In a phase 1 clinical trial in breast cancer patients, TcTM demonstrated faster injection site clearance and equivalent primary sentinel lymph node uptake when compared to TcSC, which has significant implications for surgical planning, patient convenience and health care costs. 8 In 2014, technetium TcTM replaced TcSC as the preferred lymphoscintigraphy (LS) agent for melanoma patients at our two institutions.…”
Section: Introductionmentioning
confidence: 99%